2018
DOI: 10.1007/s41116-018-0016-2
|View full text |Cite
|
Sign up to set email alerts
|

Solar prominences: theory and models

Abstract: Magnetic fields suspend the relatively cool material of solar prominences in an otherwise hot corona. A comprehensive understanding of solar prominences ultimately requires complex and dynamic models, constrained and validated by observations spanning the solar atmosphere. We obtain the core of this understanding from observations that give us information about the structure of the “magnetic skeleton” that supports and surrounds the prominence. Energetically-sophisticated magnetohydrodynamic simulations then a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
80
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 108 publications
(82 citation statements)
references
References 202 publications
(262 reference statements)
1
80
1
Order By: Relevance
“…Note also that in our event, the filament itself did not seem to reach the location of the green circle as the field lines in Figure 6 do. The filament itself likely does not represent the entirety of the erupting flux rope, since filaments are only located in the lower, dipped portions of long, flat, sheared, or twisted field lines (e.g., Gibson & Fan 2006;Dudík et al 2008;Luna et al 2012;Zuccarello et al 2016;Xia & Keppens 2016;Gibson 2018;Gunár et al 2018), while the rest of the flux rope may not be readily apparent in observations. However, as the green circle is located in a coronal dimming region (compare Figure 2a with 4d), the corresponding coronal loop likely reconnected with a flux rope field line not made visible in observations by absorbing filament plasma.…”
Section: Reconnection Of Overlying Coronal Loopsmentioning
confidence: 99%
“…Note also that in our event, the filament itself did not seem to reach the location of the green circle as the field lines in Figure 6 do. The filament itself likely does not represent the entirety of the erupting flux rope, since filaments are only located in the lower, dipped portions of long, flat, sheared, or twisted field lines (e.g., Gibson & Fan 2006;Dudík et al 2008;Luna et al 2012;Zuccarello et al 2016;Xia & Keppens 2016;Gibson 2018;Gunár et al 2018), while the rest of the flux rope may not be readily apparent in observations. However, as the green circle is located in a coronal dimming region (compare Figure 2a with 4d), the corresponding coronal loop likely reconnected with a flux rope field line not made visible in observations by absorbing filament plasma.…”
Section: Reconnection Of Overlying Coronal Loopsmentioning
confidence: 99%
“…Kuckein et al (2009Kuckein et al ( , 2012b studied an active region filament observed in July, 2005, and suggested a flux rope topology. Together, the field strengths and angles can be used to distinguish between the multiple topologies that were suggested to be able to support the filament plasma, such as the sheared arcade model and the flux rope model (Gibson 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prominences/filaments are structures formed in the solar atmosphere following magnetic polarity inversion lines. They are formed in the chromosphere by cool dense (hundred times cooler and denser than the coronal material) plasma held in place by solar magnetic fields (Engvold, 2015;Gibson, 2018;Martin, 2015). At the limb they appear as bright features when observed in few optical, extreme ultraviolet lines such as H , Ca ii K, and He ii 304 Å.…”
Section: Introductionmentioning
confidence: 99%